Demand for Food Safety Attributes for Vegetables in Malaysia - Abdul Hadi, Ahmad Hanis Izani; Radam, Alias; Shamsudin, Mad Nasir; Selamat, Jinap (Thai Society of Higher Eduction Institutes on Environment, 2010)
In a developing economy like Malaysia with rising per capita income, there have been changes in the consumer demand for food attributes such as safety, freshness, appearance and texture. This study investigated the demand for food safety attributes for vegetables. The results suggested that food safety attributes were ranked the highest for leafy and root vegetables, and ranked second behind freshness for fruit vegetables. Consumers were also willing to pay premium prices for the safety attributes. The findings would have positive implications for the agrifood industry if it responds effectively to translate into business opportunities to these changes.